Curettage and diathermy: a treatment for feline nasal planum actinic dysplasia and superficial squamous cell carcinoma. (1st February 2013) - Jarrett, R. H.; Norman, E. J.; Gibson, I. R.; Jarrett, P.
<x xml:space="preserve">Abstract</x> Objective To evaluate curettage and diathermy as a treatment for actinic dysplasia and superficial squamous cell carcinoma of the feline nasal planum. Methods Thirty‐four cats clinically assessed to have actinic dysplasia and superficial squamous cell carcinoma involving less than 50% of the nasal planum were treated with a three‐cycle curettage and diathermy procedure. Degree of dysplasia, response to treatment, adverse effects, owner perceptions, time to recurrence and proportion disease free at 1 year were evaluated. Results Lesions ranged from actinic keratoses to invasive squamous cell carcinoma. A complete response to treatment was obtained in all cats. The median follow‐up time was 18 · 2 (IQR: 12 · 0–22 · 8) months. Two cats had a clinical recurrence of lesions at 161 and 192 days after treatment. The probability of remaining disease free after 12 months was 0 · 94 (95% CI: 0 · 85–1 · 0). Median time to recurrence was not reached. The procedure was well tolerated with a good cosmetic outcome and no significant post‐operative complications. Clinical Significance This study suggests that curettage and diathermy is an effective treatment for feline actinic dysplasia and for superficial squamous cell carcinoma involving less than 50% of the nasal planum. Curettage and diathermy is an easily mastered technique, requiring minimal equipment.